2021
DOI: 10.1186/s13287-021-02401-x
|View full text |Cite
|
Sign up to set email alerts
|

SiRNA in MSC-derived exosomes silences CTGF gene for locomotor recovery in spinal cord injury rats

Abstract: Background How to obtain a small interfering RNA (siRNA) vector has become a moot point in recent years. Exosomes (Exo) show advantages of long survival time in vivo, high transmission efficiency, and easy penetration across the blood-spinal cord barrier, renowned as excellent carriers of bioactive substances. Methods We applied mesenchymal stem cell (MSC)-derived exosomes as the delivery of synthesized siRNA, which were extracted from rat bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
2
36
1
Order By: Relevance
“…A total of 701 related articles were obtained. After excluding the literature based on the exclusion criteria, eventually 32 studies were included (19)(20)(21). The entire screening process is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 701 related articles were obtained. After excluding the literature based on the exclusion criteria, eventually 32 studies were included (19)(20)(21). The entire screening process is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included 32 studies, only two studies were controlled studies ( 29 , 33 ), and the remaining 30 studies were randomized controlled studies. The species of animals included SD rats ( 19 21 , 28 37 , 39 , 40 , 42 44 , 46 , 47 , 49 53 , 55 , 56 ), Wistar rats ( 41 , 54 ), and C57BL/6 mice ( 38 , 45 , 48 ); gender included male ( 28 , 30 32 , 38 45 , 49 , 53 , 54 ) and female ( 19 , 20 , 29 , 33 , 34 , 36 , 37 , 46 48 , 50 52 , 55 , 56 ), two studies did not report the sex of the animals ( 21 , 35 ); the weights of animals were between 150 ( 41 ) and 300 g ( 20 , 44 ), the weight of the mouse was between 17 and 22 g ( 48 ), and seven of the studies did not report the weight of the animals ( 21 , 29 , 30 , 38 , 42 , 45 , 50 ); age was between 6 ( 38 , 44 , 45 , 50 , 51 ) and 12 weeks ( 47 , 56 ), and nine of the studies did not report the age of the animals ( …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently researchers illustrated that silencing the CTGF gene via siRNA-loaded MSCs-derived exosomes effectively reduced the inflammation and neuronal apoptosis at the injured area of the spinal cord. Besides, it has been shown that loading miRNA into the exosome structure can easily induce some processes such as promoting cancer cell apoptosis, regulating lipid metabolism, and promoting angiogenesis [ 114 ].…”
Section: Therapeutic Applications Of Exosomesmentioning
confidence: 99%